Abscisic acid positively regulates l‐arabinose metabolism to inhibit seed germination through ABSCISIC ACID INSENSITIVE4‐mediated transcriptional promotions of MUR4 in Arabidopsis thaliana. Issue 2 (27th September 2019) - Yan, Jingwei; Fang, Lin; Yang, Lan; He, Huan; Huang, Yun; Liu, Ya; Zhang, Aying
Summary: l ‐Arabinose (l ‐Ara) is a major monosaccharide in plant polysaccharides and glycoproteins, and functions in plant growth and development. However, the potential role of l ‐Ara during abscisic acid (ABA)‐mediated seed germination has been largely ignored. Here, our results showed a function of l ‐Ara during ABA‐mediated seed germination. ABA slowed down the reduction of l ‐Ara in seed cell wall, and exogenous l ‐Ara aggravated the inhibition of ABA on germination. We further found that MUR4, encoding URIDINE 5′‐DIPHOSPHATE‐d ‐XYLOSE 4‐EPIMERASE 1, played a vital role in ABA‐mediated germination. MUR4 was highly expressed in embryo and induced by ABA in both seeds and seedlings. Overexpression of MUR4 conferred hypersensitive seed germination and early postgermination growth to ABA. Further analysis revealed that ABSCISIC ACID INSENSITIVE4 (ABI4) positively modulated the MUR4 expression by directly binding the Coupling Element1 motif of MUR4 promoter. Consistently, abi4‐1 mutant had a lower l ‐Ara content in seed cell wall, while a higher l ‐Ara content in seed cell wall was observed in ABI4 overexpressors. Genetic analysis suggested that overexpression of MUR4 in abi4‐1 partly restored the ABA sensitivity of abi4‐1 . We established the link between ABA and l ‐Ara during ABA‐mediated seed germination and cotyledon greening in Arabidopsis and revealed the potential molecular mechanism.